Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conservation goals. One approach that shows considerable promise for addressing these challenges is adaptive management, which by now is broadly seen as a natural, intuitive, and potentially effective way to address decision-making in the face of uncertainties. Yet the concept of adaptive management continues to evolve, and its record of success remains limited. In this article, we present an operational framework for adaptive decision-making, and describe the challenges and opportunities in applying it to real-world problems. We discuss the key elements required for adaptive decision-making, and their integration into an iterative process that highlights and distinguishes technical and social learning. We illustrate the elements and processes of the framework with some successful on-the-ground examples of natural resource management. Finally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and strategic challenges.
Keywords: IMPORTANT

The relationship between adaptive management of social-ecological systems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managing social-ecological systems involving high levels of complexity and uncertainty. However, many obstacles still hamper its implementation. Law is often seen as a barrier for moving adaptive management beyond theory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this knowledge gap by providing a systematic review of the peer-reviewed literature on the relationship between adaptive management and law in relation to social-ecological systems. We analyze how the scholarship defines the concept of adaptive management, identifies the legal barriers to adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geographically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our results show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Legal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation but also to make law itself more adaptive.

Using adaptive processes and adverse outcome pathways to develop meaningful, robust, and actionable environmental monitoring programs - Arciszewski, Tim J.; Munkittrick, Kelly R.; Scrimgeour, Garry J.; Dubé, Monique G.; Wrona, Fred J.; Hazewinkel, Rod R. (Integrated Environmental Assessment and Management, 2017)
The primary goals of environmental monitoring are to indicate whether unexpected changes related to development are occurring in the physical, chemical, and biological attributes of ecosystems and to inform meaningful management intervention. Although achieving these objectives is conceptually simple, varying scientific and social challenges often result in their breakdown. Conceptualizing, designing, and operating programs that better delineate monitoring, management, and risk assessment processes supported by hypothesis-driven approaches, strong inference, and adverse outcome pathways can overcome many of the challenges. Generally, a robust monitoring program is characterized by hypothesis-driven questions associated with potential adverse outcomes and feedback loops informed by data. Specifically, key and basic features are predictions of future observations (triggers) and mechanisms to respond to success or failure of those predictions (tiers). The adaptive processes accelerate or decelerate the effort to highlight and overcome ignorance while preventing the potentially unnecessary escalation of unguided monitoring and management. The deployment of the mutually reinforcing components can allow for more meaningful and actionable monitoring programs that better associate activities with consequences. Integr Environ Assess Manag 2017;13:877–891. © 2017 The Authors. Integrated Environmental Assessment and Management Published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC)
Keywords: Adaptive monitoring; Environmental management; Environmental monitoring; Tier; Trigger

Adaptive environmental assessment and management: a new approach to environmental impact assessment - Jones, Michael L.; Greig, Lorne A. (New directions in environmental impact assessment in Canada, 1985)

Adaptive Management in the Courts - Fischman, Robert L.; Ruhl, J.B. (Minnesota Law Review, 2010)
Adaptive management has become the tonic of natural resources policy. With its core idea of “learning while doing,” adaptive management has infused the natural resources policy world to the point of ubiquity, surfacing in everything from mundane agency permits to grand presidential proclamations. Indeed, it is no exaggeration to suggest that these days adaptive management is natural resources policy. But is it working? Does appending “adaptive” in front of “management” somehow make natural resources policy, which has always been about balancing competing claims to nature’s bounty, something more and better? Many legal and policy scholars have asked that question, with mixed reviews. Their evaluations, however, have rested on theory, program-specific surveys, and isolated case studies. This article provides the first comprehensive review of adaptive management from the perspective that likely matters most to the natural resource agencies practicing adaptive management - how is it faring in the courts? Part I of the Article examines the theory, policy, and practice of adaptive management, focusing on the experience of the federal resource management agencies. The end product in practice is something we call “a m-lite,” a watered down version of the theory that resembles ad hoc contingency planning more than it does planned “learning while doing.” This gap between theory and practice leads to profound disparities between how agencies justify decisions and how adaptive management in practice arrives at the courthouse doorsteps. In Part II we review how these disparities have played out in courts considering claims that agency practice of adaptive management has not lived up to its theoretical promise or to the legal demands of substantive and procedural environmental law. We extract three key themes from the body of case law in this respect. Part III extends from the existing case law to draw lessons for agencies and Congress about the future practice of adaptive management. Our ultimate message to agencies is that a m-lite can be an effective decision method - and one that survives judicial scrutiny - but agencies must be more disciplined about its design and implementation. This includes resisting the temptation to employ adaptive management to dodge burdensome procedural requirements, substantive management criteria, and contentious stakeholder participation. If faithfully followed and enforced, this model, despite its flaws, could serve as an important component of natural resources policy to confront problems of the future as daunting as climate change.

Adaptive Management of Renewable Resources - Walters, C. J. (Macmillan Publishers Ltd, 1986)
The author challenges the traditional approach to dealing with uncertainty in the management of such renewable resources as fish and wildlife. He argues that scientific understanding will come from the experience of management as an ongoing, adaptive, and experimental process, rather than through basic research or the development of ecological theory. The opening chapters review approaches to formulating management objectives as well as models for understanding how policy choices affect the attainment of these objectives. Subsequent chapters present various statistical methods for understanding the dynamics of uncertainty in managed fish and wildlife populations and for seeking optimum harvest policies in the face of uncertainty. The book concludes with a look at prospects for adaptive management of complex systems, emphasizing such human factors involved in decision making as risk aversion and conflicting objectives as well as biophysical factors. Throughout the text dynamic models and Bayesian statistical theory are used as tools for understanding the behavior of managed systems. These tools are illustrated with simple graphs and plots of data from representative cases. This text/reference will serve researchers, graduate students, and resource managers who formulate harvest policies and study the dynamics of harvest populations, as well as analysts (modelers, statisticians, and stock assessment experts) who are concerned with the practice of policy design.

Developing an effective adaptive monitoring network to support integrated coastal management in a multiuser nature reserve - Vugteveen, Pim; van Katwijk, Marieke M.; Rouwette, Etiënne; Lenders, H. J. Rob; Hanssen, Lucien (Ecology and Society, 2015)
ABSTRACT. We elaborate the necessary conceptual and strategic elements for developing an effective adaptive monitoring network to support Integrated Coastal Management (ICM) in a multiuser nature reserve in the Dutch Wadden Sea Region. We discuss quality criteria and enabling actions essential to accomplish and sustain monitoring excellence to support ICM. The Wadden Sea Long-Term Ecosystem Research project (WaLTER) was initiated to develop an adaptive monitoring network and online data portal to better understand and support ICM in the Dutch Wadden Sea Region. Our comprehensive approach integrates ecological and socioeconomic data and links research-driven and policy-driven monitoring for system analysis using indicators of pressures, state, benefits, and responses. The approach and concepts we elaborated are transferable to other coastal regions to accomplish ICM in complex social-ecological systems in which scientists, multisectoral stakeholders, resource managers, and governmental representatives seek to balance long-term ecological, economic, and social objectives within natural limits.
Keywords: IMPORTANT

Compass and Gyroscope: Integrating Science and Politics in the Environment - Lee, Kai N. (Island Press, 1993)
In this original and far-reaching synthesis, Kai N. Lee explains that together science and politics can lead the waytoward the sustainable management of the world’s resources. Rigorous science can act as our compass, pointingus toward greater and more useful knowledge (adaptive management), and practical politics can serve as our gyroscope, keeping usbalanced between competing interest groups. Unlike some approaches to sustainable development, Compass and Gyroscope is refreshingly grounded in the realworld. Lee explains that sustainability cannot occur overnight, we have neither an adequate base of knowledgenor a reliable means of properly implementing and executing management plans. "Sustainable development is not a goal, not a condition likely to be attained on earth as we know it. Rather it is more like freedom or justice,a direction in which we strive..." Using the Columbia River Basin in the Pacific Northwest as a case study, Lee examines the successes andfailures of past and present management. He describes what has been learned, and explains how that experiencecan be applied to environmental management generally. Throughout, the author delves deeply into the theoretical framework behind the real-world experience, exploring how theories of science, politics, and cognitive psychology can be integrated into environmental management.

Adaptive environmental assessment and management - Holling, C. S. (International series on applied systems analysis, 1978)
Keywords: Ecology; Economic development; Environmental impact analysis; Environmental protection

Resilience Thinking: Sustaining Ecosystems and People in a Changing World - Walker, Brian; Salt, David; Reid, Walter V. (Island Press, 2006)
Increasingly, cracks are appearing in the capacity of communities, ecosystems, and landscapes to provide the goods and services that sustain our planet's well-being. The response from most quarters has been for "more of the same" that created the situation in the first place: more control, more intensification, and greater efficiency. "Resilience thinking" offers a different way of understanding the world and a new approach to managing resources. It embraces human and natural systems as complex entities continually adapting through cycles of change and seeks to understand the qualities of a system that must be maintained or enhanced in order to achieve sustainability. It explains why greater efficiency by itself cannot solve resource problems and offers a constructive alternative that opens up options rather than closing them down. In "Resilience Thinking", scientist Brian Walker and science writer David Salt present an accessible introduction to the emerging paradigm of resilience. The book arose out of appeals from colleagues in science and industry for a plainly written account of what resilience is all about and how a resilience approach differs from current practices. Rather than complicated theory, the book offers a conceptual overview along with five case studies of resilience thinking in the real world. It is an engaging and important work for anyone interested in managing risk in a complex world.